A Critical Industrial Relations Approach to Understanding Contemporary Worker Uprising. Issue 3 (August 2023) - Lee, Tamara L.; Tapia, Maite
Consistent with our calls for critical approaches to traditional Industrial Relations questions, we argue that it is important to consider whether the "major upsurge in union organizing" is more accurately framed as a continuation of long-running democracy fights against systemic inequity and injustice. Thus, we bring focus to "whole worker" organizing, as well as the structural limitations of our labor laws and institutions, to illuminate counter-narratives to the way we tell stories about contemporary worker organizing.